Bodo od evropskega socialnega dialoga ostali samo še nezavezujoči dogovori? - Franca, Valentina (Delavci in delodajalci, 2017)
On the basis of the development of the European social dialogue and current events, the article introduces the issue of implementation of agreements reached among European social partners to the legislations of the EU member countries. The diversity of agreements, non-uniform practice, different power of national social partners, and weak role of the European Commission result in unequal position of workers. In order to preserve and strengthen the social dialogue at the European level it is also required to resist the tendency of making the outcomes of social dialogue non-binding and less and less social.
Keywords: delodajalci; Evropska unija; mednarodni sporazumi; sindikati; socialni dialog; socialno partnerstvo